2018
DOI: 10.1093/neuros/nyy081
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Neoplasms in the First Year of Life: Results of a Third Cohort of Patients From a Single Institution

Abstract: Overall survival from neonatal brain tumors remains similar to previous series; analysis of tumor subtypes reveals improvements for CPP and gliomas. Despite increasing operative intervention, operative mortality continues to decline for this group of challenging patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…The expanded upper roof plate in Lcre;Ptch cko ;NICD1 mice is consistent with the developmental origin and cilia defect of CPC being driven by NOTCH and SHH signaling. These animals represent an ideal therapeutic model for congenital or infantile CPC, a rare condition associated with high morbidity and mortality [ 50 , 51 ]. Indeed, NOTCH inhibition by IMR-1 rescued the cilia deficit by inducing multiciliated tumor cells, whereas SHH pathway inhibitors suppressed tumor cell proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expanded upper roof plate in Lcre;Ptch cko ;NICD1 mice is consistent with the developmental origin and cilia defect of CPC being driven by NOTCH and SHH signaling. These animals represent an ideal therapeutic model for congenital or infantile CPC, a rare condition associated with high morbidity and mortality [ 50 , 51 ]. Indeed, NOTCH inhibition by IMR-1 rescued the cilia deficit by inducing multiciliated tumor cells, whereas SHH pathway inhibitors suppressed tumor cell proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The enlarged roof plate in Lcre;Ptch cko ; NICD1 animals is consistent with the developmental origin and cilia defect of CPC driven by NOTCH and SHH signaling. These animals serve as ideal therapeutic models for congenital or infantile CP tumors, a rare condition associated with high morbidity and mortality (Crawford and Isaacs 2019; Toescu et al 2019). Indeed, NOTCH inhibition by IMR-1 rescued the cilia deficit by forming multiple cilia and decreasing mitosis in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognosis of patients with central nervous system tumors was markedly different in our study. Toescu et al 12 reported that choroid plexus papilloma occurred within 1 year of age, followed by low‐grade glioma with a mortality rate of 0%, which required multiple operations. Intracranial primitive neuroectodermal tumors had a 5‐year survival rate of 0%.…”
Section: Discussionmentioning
confidence: 99%